PENGARUH E-WOM TERHADAP PURCHASE DECISION PADA AYAM BETUTU BU LINA GILIMANUK, BALI - Jocelyn Nie; Ferawati Angelita; Yolanda Febryna; Amelia; Vanesya Beatrix; Christopher Chendra; Jerry Wijaya (Journal of Applied Management Studies, 2023)
E-WOM, as one of the marketing techniques developed from the old marketing technique namely Word-of-mouth by adapting digital technology, becomes one of the effective marketing techniques. The purpose of this study is to analyze the effect of e-WOM and customer satisfaction towards purchase decision. The object used is "Ayam Betutu Bu Lina'' in Gilimanuk, Bali. The methods used in this study are descriptive and causal methods with a quantitative approach. This study used primary data obtained from the distribution of the online questionnaires to 230 respondents, and the secondary data from other references. Primary data processing in this study utilized IBM SPSS Statistic and AMOS 26 Software using SEM (Structural Equation Modeling) as the research model. The results of this study showed that e-WOM has a positive and significant effect on the purchase decision. In addition, customer satisfaction also has a positive and significant effect on the purchase decision.